ENTERPRISE ARCHITECTURE WITH TOGAF IN THE INDONESIAN FOOTWEAR INDUSTRY, CASE STUDY AT XYZ FOOTWEAR INDUSTRY - Vinardo; Dazki, Erick; Eko Indrajit, Richardus (Informatika, Universitas Jenderal Soedirman, 2023)
The footwear industry is one of the industries that absorbs a lot of labor force, and automatically this industry has a great impact on the economic growth of the local community. The competition in the footwear industry involves global competition with footwear industries from all over the world. Companies that can provide good quality and efficient costs will be the choice for production places for various world footwear brands. The use of appropriate and integrated information technology that covers all processes, both internal and external company processes, will increase the operational effectiveness of the company. The design of this information technology utilization is built by adopting the TOGAF framework. TOGAF is a standard methodology and framework for enterprise architecture that has been widely used by leading organizations in the world to improve their business effectiveness and efficiency by utilizing information technology. This journal will provide design and implementation of TOGAF standards in the footwear industry, with study case at XYZ footwear industry to deliver enterprise architecture for footwear industry in Indonesia, so they can improve competitiveness among other footwear industry globally.